Crystalline Orientation–Dependent Spin Hall Effect in Epitaxial Platinum - Xiao, Yuxuan; Wang, Hailong; Fullerton, Eric E. (Frontiers in Physics, 2022)
We report on the spin Hall effect in epitaxial Pt films with well-defined crystalline (200), (220) and (111) orientations and smooth surfaces. The magnitude of the spin Hall effect has been determined by spin-torque ferromagnetic resonance measurements on epitaxial Pt/Py heterostructures. We observed a 54% enhancement of the charge-to-spin conversion efficiency of the epitaxial Pt when currents are applied along the in-plane <002> direction. Temperature dependent harmonic measurements on epitaxial Pt/Co/Ni heterostructures compared to a polycrystalline Pt/Co/Ni suggest the extrinsic mechanism underlying spin Hall effect in epitaxial Pt. Our work contributes to the development of energy-efficient spintronic devices by engineering the crystalline anisotropy of nonmagnetic metals.